Revisiting the aerobic capacity of Notosuchia (Crocodyliformes, Mesoeucrocodylia) - Sena, Mariana V. A.; Montefeltro, Felipe C. [UNESP]; Marinho, Thiago S.; Langer, Max C.; Fachini, Thiago S.; Pinheiro, Andre E. P.; Machado, Alessandra S.; Lopes, Ricardo T.; Pellarin, Romain; Sayao, Juliana M.; Oliveira, Gustavo R.; Cubo, Jorge (Scandinavian University Press, 2024)
This study examines the metabolic rates of notosuchian crocodyliforms. Although predominantly composed of terrestrial forms, the group also encompasses the putatively semi-aquatic itasuchids. The notosuchian record is particularly rich in Brazil and Argentina, which provides a basis for understanding their ecology and physiology. This research expands a previous study that investigated the aerobic capacities of these organisms, considering blood flow rate (Q̇ ) in the femoral nutrient artery as a proxy to infer their maximal aerobic metabolic rates, critical for understanding peak aerobic performance during strenuous activities. Femoral nutrient foramina act as conduits for the major blood supply to the bone and are correlated with aerobic capacity, providing insights into the physiological capabilities of the studied taxa. This study revisits and expands upon a previous dataset by including additional taxa and provides more precisely adjusted mass-independent maximal metabolic rate predictions for the sample of Notosuchia. We incorporate data from a broader spectrum of extant tetra-pods and employ Phylogenetic Eigenvector Maps (PEM) to refine our analyses. PEM allow the inclusion of an auxiliary predictor related to the response variable, alongside phylogenetic eigenvectors. The results indicate notosuchians possessed higher mass-independent maximal metabolic rates (MMRs) than extant Crocodylia, and lower than those of extant varanid lizards, which suggests an elevated aerobic capacity, enabling a more active lifestyle compared to extant crocodylians. The study addresses previous miscalculations for the body mass exponent on the MMR unit. We introduce Q̇ values based on the nutrient femoral artery lumen area instead of the total area of the nutrient foramen, and provide a corrected MMR for Crocodylus porosus, allowing more accurate predictions of notosuchian aerobic capacities. This research reveals metabolic flexibility within crocodyliforms, with an elevated aerobic capacity allowing notosuchians to sustain vigorous activities, possibly related to their terrestrial adaptations and active foraging strategies.
Keywords: Bone; femoral nutrient foramina; metabolic rates; Notosuchia; Phylogenetic Eigenvector Maps